Bayberry Whitefly, Parabemisia myricae (Kuwana) (Insecta: Homoptera: Aleyrodidae: Aleyrodinae) - Avas B. Hamon; Ru Nguyen; Harold Browning (EDIS)
The whitefly, Bemisia myricae, was described by Kuwana (1927) from Japan on the hosts Myrica rubra, Morus alba, and Citrus. Takahashi (1952) transferred this whitefly to the genus Parabemisia because of long marginal setae on the so-called "pupal" case and blunt lateral tubercles at the base of the lingula.  This document is EENY-138 (originally published as DPI Entomology Circular No. 328), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2000. Revised: November 2002.